In Search of the ‘Spirit of Capitalism’: About Normative Mechanisms Responsible for the Organisation of Social Behaviours - Kutyło, Łukasz (Annales. Etyka w Życiu Gospodarczym, 2018)
The starting point for my reflections was a thesis presented by Max Weber more than one hundred years ago. According to this thesis, a Protestant ethos was an important factor responsible for the spectacular economic growth of Northern Europe. In his own reflections, the German scholar paid attention mainly to both Protestant asceticism, which concentrated the energy of believers on the work they did, as well as on theology, especially Calvinism, which provided explanations for hard work and the accumulation of capital. It seems, however, that in his reconstruction of the Protestant ethos, Weber described universal mechanisms which are responsible for social mobilization in general. The problem is that instead of trying to analyze them, he ultimately concentrated on their cultural manifestations. The main aim of my paper is an identification of these mechanisms. They discipline individuals, or more correctly, they discipline the patterns of playing these social roles, which are functionally significant for initiating and sustaining the mobilization process. In other words, when there is a need in a society to achieve specific goals, including economic ones, it should develop social norms which will be able to bolster the engagement of its members and focus their energy on specific aspects of their life. Moreover, there is a need to prepare non‑normative mechanisms, which increase the probability that members of the society will adhere to these social norms. The reflections in this regard seem to be important mainly for developing states. On the one hand, they should prepare mechanisms which allow them to develop their economies. On the other hand, the members of these states must face many costs associated with their implementation and this problem should also be a part of the discussion.